Комп’ютерні засоби зовнішнього моніторингу великих об’єктів з використанням сенсорних мереж - Дєєв, С. Д. (ХНУРЕ, 2023)
То ensure operation, it is proposed to carry out testing of the sensor network using anchor nodes with a global positioning system, for localization when deploying the network and ensuring its normal operation. The number of test nodes is determined by the Hamming number depending on the total number of nodes used. This means that the more nodes in the network, the more test nodes are needed to diagnose our system and obtain correct data. Also it should provide correct result for all customers who will use it in a right way regarding instruction.